Riwayat Berat Badan Lahir Rendah (BBLR) Dan Pemberian ASI Eksklusif Berkontribusi Terhadap Kejadian Stunting Pada Anak Usia 12 sampai 24 Bulan - Linda Andri Mustofa Mustofa (STIKES dan AKZI Karya Husada Kediri, 2023)
Malnutrition is a leading cause of stunting in children in low- and middle-income nations. Stunting is a result of a lack of proper nutrition, recurring infections, or chronic illnesses that impair nutrient intake, absorption, and utilisation. Every nation, including Indonesia, needs to pay attention to stunting management because, if it is not addressed, it will have both short- and long-term effects on physical and cognitive disorders, decreased productivity, health status, and even an adult's risk of developing degenerative diseases. Efforts to prevent and promote health are thought to be more cost-effective in addressing the issue of stunting. The aim of this study was to investigate the association between stunting and LBW history and exclusive breastfeeding. Correlational analytic research using a retrospective cohort approach was the method adopted in this study. The dependent variable was the prevalence of stunting, whereas the independent factors in the study were LBW and exclusive breastfeeding. The population included all children aged 24-48 months in Sejati village, Camplong sub-district, Sampang district from 14 to 22 June 2023. The sample of 69 children was selected by random sampling method. Data were collected using leaf collection tools from data sources derived from secondary data. Processed data is collected and analyzed through editing, coding, scoring, and tabulation. Data analysis used a 5% redundancy factor (C) test. The study demonstrates that there is a relationship between LBW and exclusive breastfeeding with the Contingency Factor (C) Test values ​​of 0.000 and 0.000. It was concluded that infants who were exclusively breastfed and were born with normal weight were less likely to be stunted than those who were exclusively breastfed and were not exclusively breastfed.